The European Variation Archive: a FAIR resource of genomic variation for all species. Issue Volume 50:Issue D1(2022) (28th October 2021) - Cezard, Timothe; Cunningham, Fiona; Hunt, Sarah E; Koylass, Baron; Kumar, Nitin; Saunders, Gary; Shen, April; Silva, Andres F; Tsukanov, Kirill; Venkataraman, Sundararaman; Flicek, Paul; Parkinson, Helen; et al.
Abstract: The European Variation Archive (EVA; https://www.ebi.ac.uk/eva/ ) is a resource for sharing all types of genetic variation data (SNPs, indels, and structural variants) for all species. The EVA was created in 2014 to provide FAIR access to genetic variation data and has since grown to be a primary resource for genomic variants hosting >3 billion records. The EVA and dbSNP have established a compatible global system to assign unique identifiers to all submitted genetic variants. The EVA is active within the Global Alliance of Genomics and Health (GA4GH), maintaining, contributing and implementing standards such as VCF, Refget and Variant Representation Specification (VRS). In this article, we describe the submission and permanent accessioning services along with the different ways the data can be retrieved by the scientific community.